2014
DOI: 10.1590/0103-8478cr20130175
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência energética de um trator agrícola utilizando duas configurações de tomada de potência

Abstract: RESUMO A tomada de potência (TDP) de um trator agrícola tem por principal fi nalidade transmitir a potência gerada no motor, para acionamento de órgãos ativos das máquinas agrícolas. Tendo em vista a necessidade de se aumentar a efi ciência energética na ABSTRACTThe agricultural tractor power take-off main purpose is to transmit the power generated in the engine to drive the active organs of farm machinery. In view of the need to increase the energy effi ciency in agriculture, some manufacturers provide for fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
6
1
1
Order By: Relevance
“…The fuel consumption measured in this study showed greater variability than the one estimated by LEITE et al (2011), VALE et al (2011), SPAGNOLO et al (2012, CHIODEROLI et al (2014) and FRANTZ et al (2014), whose variation coefficients were 3.34; 5.73; 1.31; 5.28 and 3.17%, respectively. However, they approached the ones determined by SOUZA et al (2015) between 6.05 and 15.12%.These discrepancies agree with the expected because this study used a larger number of operating conditions for agricultural equipment, given by the three gear and three engine speeds in order to increase the range of fuel consumption, which justifies high fluctuations around the average.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…The fuel consumption measured in this study showed greater variability than the one estimated by LEITE et al (2011), VALE et al (2011), SPAGNOLO et al (2012, CHIODEROLI et al (2014) and FRANTZ et al (2014), whose variation coefficients were 3.34; 5.73; 1.31; 5.28 and 3.17%, respectively. However, they approached the ones determined by SOUZA et al (2015) between 6.05 and 15.12%.These discrepancies agree with the expected because this study used a larger number of operating conditions for agricultural equipment, given by the three gear and three engine speeds in order to increase the range of fuel consumption, which justifies high fluctuations around the average.…”
Section: Resultscontrasting
confidence: 55%
“…The influence of the technical characteristics of the mechanized set, gears and rotations in the tractor engine on fuel consumption is confirmed on the study of MOUNTAIN et al (2011), VALE et al (2011), SPAGNOLO et al (2012), FRANTZ et al (2014, FEITOSA et al (2015), FIORESE et al (2015) and SOUZA et al (2015). However, in these studies, the functional dependencies to determine this consumption were not established.…”
Section: Introductionmentioning
confidence: 95%
“…Alternative managing options for mechanized agricultural operations are being searched for, more specifically for the main source of power for them, the farm tractor, because of the costs of fuel, pollution generated by their combustion, and the necessity of diminishing energy consumption (Frantz et al, 2014). Tractor use in rural areas is very diverse, and the search for the optimized performance is justifiable (Vale et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The growing environmental concern constrains the use of fossil fuels, which are the main responsible for the emission of pollutant gases in the atmosphere (Frantz et al, 2014). Global energy consumption and the adverse environmental effects of its use have had significant increases in the past century and are projected to continue to increase in the future (Janulevicius et al, 2013;Lebedevas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%